LEGAL CONTENT OF AUTHONOMY AND PECULIARITIES OF AUTHONOMOUS BODIES IN THE REPUBLIC OF ARMENIA - Manasyan, Anahit (State and Law, 2021)
The article considers issues with regard to autonomous bodies in the Republic of Armenia. A thorough analysis is provided on differentiation of concepts “autonomy” and “independence”, the content of these terms is revealed. The status and peculiarities of autonomous bodies in the Republic of Armenia are presented in the light of the history of development of the latter both in Armenia and in various other states. The guarantees of independence of autonomous bodies are also analyzed in the article.